HSP70CA2 is associated with cytoskeletal, membrane repair, and chaperone responses during acute heat shock in Urechis unicinctus - Dawei Lin; Yuxin Feng; Wenwen Jiang; Ying Lu; Wenqing Zhang; Long Zhang; Zhifeng Zhang; Yubin Ma (Marine Pollution Bulletin, 2026)

Liensinine can improve vascular remodeling in hypertension through the ferroptosis-related TLR4 inflammatory pathway - Daxin Chen; Peizhi Jia; Meiling Wang; Baojie Du; Haitao Du; Xi Huang; Jianwei Zeng; Qiaoyan Cai; Ling Zhang; Ying Zhu; Shan Lin; Dawei Lian; et al. (Journal of Molecular Medicine, 2026)

Identification of sex determination region and development of sex-specific markers using genome re-sequencing in Urechis unicinctus (Annelida, Echiura) - Dawei Lin; Xixi Li; Zhifeng Zhang; Zhenkui Qin (Aquaculture, 2026)

Multifunctional CaO-enabled persulfate activation for pentachlorophenol degradation in contaminated soil: Calcium-mediated transformation and oxidative enhancement - Dawei Lan; Ping Liu; Fengjiao Zhang; Jiang Lin; Ying Ran; Wan Cheng; Jing Chen; Xiaohui Wu; Anxu Sheng; Linling Wang (Journal of Environmental Chemical Engineering, 2026)

A Machine learning based analysis for ignition strategies and mechanisms of High-Efficiency renewable methanol combustion: Diesel-Piloted and turbulent jet ignition engines - Peng Wang; Wuqiang Long; Dawei Lin; Pengbo Dong; Yang Wang; Hua Tian; Wentao Zhao; Mengfan Wang; Qianming Wang; Yongjian Wang (Fuel, 2026)

Understanding phage dynamics and their potential roles during soy sauce fermentation using metagenome-assembled genomes - Guiliang Tan; Shaohan Qi; Min Hu; Dawei Wang; Kaiwen Lin; Yi Wang; Sui Chen; Qingyu Zhang; Lichao Zhao (Food Research International, 2026)

Surface-reconstructed manganese oxides for enhanced external-oxidant-free degradation of bisphenol A: A direct electron transfer mechanism - Dawei Wang; Yihan Zhu; Keyi Gao; Zhuang Liu; Tong Li; Lin Chen; Yilan Jiang (Chemical Engineering Journal, 2026)

Acid-catalyzed ethanol pretreatment of sugarcane bagasse enables electrochemically improved hard carbon anodes for sodium-ion batteries - Nethmi Kulanika Dayarathne; Eric Campbell; Mu Xiao; Jiaye Ye; Cheng Yan; Hongxia Wang; Dawei Wang; Yu Lin Zhong; Zhanying Zhang (Chemical Engineering Journal, 2026)

Role of Glass Transition Mismatch in Rice Quality Deterioration During Hot-Air Drying - Wenting Xu; Yafang Shao; Xiaoyan Lin; Yaling Chen; Dawei Zhu (Journal of Cereal Science, 2026)

Machine learning Identifies the impacts of the Eastern route of the South-to-North water diversion Project on the transformation of dissolved organic matter - Na Huang; Penghui Li; Yilan Jiang; Lin Chen; Dawei Wang (Journal of Hydrology, 2026)

Radio frequency-enhanced remediation of PAHs-contaminated soils using peroxydisulfate: Performance and mechanistic insights - Wenhao Qi; Anxu Sheng; Dawei Lan; Zezhou Zhao; Yao Shi; Fengjiao Zhang; Jiang Lin; Ying Ran; Wei Lou; Jing Chen; Xiaohui Wu; Linling Wang (Journal of Environmental Management, 2026)

Socioeconomic drivers of riverine biochemical oxygen demand: Insights from interpretable machine learning - Na Huang; Dawei Wang; Penghui Li; Lin Chen; Wei Wang; Zeng Zhou; Pei Xu; Sile Li; Yali Zhang; Yilan Jiang (Journal of Environmental Management, 2026)

Identification of candidate genes and SNPs associated with high temperature tolerance by genome-wide association study (GWAS) in Urechis unicinctus (Annelida, Echiura) - Dawei Lin; Ying Lu; Long Zhang; Yuxin Feng; Wenwen Jiang; Zhifeng Zhang; Yubin Ma (Aquaculture, 2026)

High-Efficiency N-acetylneuraminic acid biosynthesis in plasmid-free Escherichia coli MG1655 - Qian Lin; Yuanlin Liu; Wenbo Zhang; Liping Qiao; Yingying Zhu; Dawei Ni; Wanmeng Mu (Bioresource Technology, 2026)

Inorganic nitrogen in inflowing water governs dissolved organic matter transformation regulated by sediments in recipient basin - Dawei Wang; Na Huang; Xin Hou; Lin Chen; Yilan Jiang; Shuhan Liu; Shishu Zhu (Water Research, 2026)

Posttranslational regulation of TOR kinase activity controls resource allocation between plant growth and immunity in Arabidopsis - Jianwei Li; Ran Wang; Chenying Li; Xijie Guo; Qinghong Li; Zhixuan Wu; Shanshan Zeng; Fan Qi; Yuchen Wang; Zhiyi Jia; Weiwei Yu; Zeming Huang; et al. (Molecular Plant, 2026)

Photo-transformation of dissolved organic matter coupled with iron minerals upon hydrological particulate resuspension-settlement - Na Huang; Yiying Wang; Yin Lu; Xuyin Yuan; Yilan Jiang; Lin Chen; Shishu Zhu; Shouliang Huo; Dawei Wang (Journal of Hydrology, 2026)

Combined effects of polystyrene micro-/nano-plastics and imidacloprid on Gut–Brain axis and neurotoxicity in juvenile Carassius auratus - Xinzi Guo; Lin Peng; Zhaoxuan Zhu; Shuocheng Fan; Jiasen Feng; Xingxing Fang; Dawei Guo; Ping Yang (Journal of Environmental Management, 2026)

Exploring the spoilage mechanism differences of yak and cattle meat during chilled storage: A combined 16S rRNA gene sequencing and non-targeted metabolomics approach - Zhoulin Wu; Sha Zhu; Chunrong Wu; Dawei Jing; Jiamin Zhang; Lin Yang; Xinhui Wang; Yongjie Wang (Food Research International, 2026)

Shear-tension interaction behavior and design model for ECC-embedded stud connectors - Li Xu; Bo Jiang; Jingting Lin; Dawei Gu; Jinlong Pan (Engineering Structures, 2026)

PET imaging-guided biomimetic nanoplatform reprograms the tumor immune microenvironment and disrupts stromal barriers to potentiate immunotherapy in malignancy - Yuan Feng; Wenyu Song; Zhaoguo Lin; Zihan Zhang; Wenzhu Hu; Xingyi Wang; Yueling Deng; Yongkang Gai; Zi Ye; Dawei Jiang; Xiaoli Lan; Xiao Zhang (Chemical Engineering Journal, 2026)

Unveiling the effects of reactor configurations on the performance of lignin removal in the ozone micro-nano-bubble system - Yin Lu; Xuyin Yuan; Haiming Kan; Chi Zhang; Lin Chen; Alessandro Gottuso; Francesco Parrino; Tong Li; Shishu Zhu; Dawei Wang (Chemical Engineering Journal, 2026)

Endogenous formation of Fe-bearing particles and their differentiation from exogenous exposure - Yuming Huang; Lin Liu; Hang Yang; Huixuan Yi; Xiangyu Li; Linqian Li; Dawei Lu; Qian Liu; Guibin Jiang (Journal of Environmental Sciences, 2025)

Glacial-interglacial climate modulates sedimentary sulfur cycling in the Peruvian oxygen minimum zone: Mechanistic insights from pyrite multiple sulfur isotopes - Xiaoxiao Yu; Fang Qian; Xiaomin Lin; Longye Du; Jianghao Bai; Dawei Lv; Yanguang Liu; Gangjian Wei; Mang Lin (Geochimica et Cosmochimica Acta, 2025)

Investigation on uniaxial tensile properties of prestressed C-GFRCM plates based on explainable machine learning algorithm - Xuhua Lin; Dawei Zhang; Zhiyu Xie; Shiji Sun; Yusen Wu (Engineering Structures, 2025)

Hollow NiS/MnS microspheres: Synergistic effects of hierarchical porosity and heterointerfaces for ultrahigh-rate supercapacitors - Minyi Lin; Zhuodi Chen; Maochan Li; Yuxuan Liu; Xiaoming Lin; Yongbo Wu; Zhiguang Xu; Dawei Wang (Chemical Engineering Journal, 2025)

Enhancement of Bacillus subtilis inactivated Microcystis aeruginosa by shaped biochar: Performance and mechanism study - Aoxue Yu; Qili Peng; Dawei Zhou; Jiangfang Yu; Naif Abdullah Al-Dhabi; Bo Peng; Yanzhong Tan; Wangwang Tang; Lin Tang (Journal of Hazardous Materials, 2025)

Green synthesis of tea polyphenol grafted epoxypropyl polymer with enhanced mechanical and antifungal benefits for bamboo protection - Haojun Lin; Haiyan Yang; Jing Yang; Dawei Wang; Zhengjun Shi; Chun Shi (Chemical Engineering Journal, 2025)

Multi-level resource utilization of food-grade nanomaterials from brewing residues: Synergistic polyphenol-pullulan membranes for litchi preservation - Congyu Lin; Peiqi Lu; Peihang Li; Zhimin Zhang; Jingqiu Ma; Yunfei Hou; Xiao Han; Zhongwei Ji; Zhilei Zhou; Dawei Li; Jian Mao (Chemical Engineering Journal, 2025)

Boosting the initial Coulombic efficiency of Bi2S3-based anode for practical sodium-ion batteries - Lankun Shi; Rongji Jiao; Dawei Lan; Li Wang; Yu Gao; Meng-Fang Lin; Zhongmin Lang; Wenxiu He; Guixiao Jia; Jinlong Cui; Shaohui Li (Chemical Engineering Journal, 2025)

Generative deep learning model assisted multi-objective optimization for wastewater nitrogen to protein conversion by photosynthetic bacteria - Pengfei Hou; Duofei Hu; Shiqi Liu; Guangming Zhang; Jinsong Liang; Huize Liu; Jizheng Zhang; Xueliang Sun; Dawei Lin; Chengxun Chen; Longfei Liu; Weilin Cai (Bioresource Technology, 2025)

Artificial neural network-based ground motion prediction equations for Sichuan-Yunnan area of China - Jianwen Cui; Dawei Lu; Shuo Xu; Guoliang Lin; Yahong Shen; Zhihao Cui (Acta Geophysica, 2025)
This study presents a novel ground motion prediction equation (GMPE) for the Sichuan-Yunnan region of China based on artificial neural networks (ANNs). Utilizing data from 207 earthquake events and 3537 ground motion recordings collected since 2007, the ANN-based GMPEs predict peak ground acceleration (PGA) and pseudo-spectral acceleration (PSA) for periods ranging from 0.04 to 6.0 s. The model incorporates five key parameters: magnitude, epicentral distance, site conditions (represented by the predominant period $${T}_{0}$$ T 0 derived from horizontal-to-vertical spectral ratios HVSR), hypocentral depth, and styles of faulting. A weighted loss function is employed during ANN training to address data imbalances, particularly the scarcity of near-field recordings. Residual analyses indicate that both inter-event and intra-event variabilities fall within acceptable limits. Comparisons with observed ground motions and existing GMPE commonly used in China confirm that the proposed ANN-based GMPE effectively captures key ground motion characteristics.

Characteristics of orographic clouds and associated mechanisms in the Qilian Mountains, northeastern Tibetan Plateau based on FengYun-4A satellite TBB product - Yi Chang; Qianrong Ma; Peng Qi; Xueliang Guo; Dawei Lin; Lijun Guo; Di Di; Yang Zhao; Hui Wang; Tianyu Chen (Atmospheric Research, 2025)

The role of IFT20 mediated by neuropeptide FILa1 in ciliary activity during larval settlement of Urechis unicinctus - Long Zhang; Wenqing Zhang; Wenyuan Lai; Zhi Yang; Dawei Lin; Zhengrui Zhang; Zhifeng Zhang (Frontiers in Marine Science, 2025)
Background Settlement and metamorphosis are crucial developmental events in the life cycles of most marine benthic invertebrates. Neuropeptides play an important role in inducing larval settlement. However, studies on the ciliary genes and the few studies have examined the pathways regulated by neuropeptides during larval settlement. Methods Here, we employed multiple molecular biology techniques to identify a ciliary gene, intraflagellar transport protein 20 ( IFT20 ) which played a significant role in the larval settlement of Urechis unicinctus (Annelida, Echiura), and revealed the related gene pathway of IFT20 expression regulated by FILa1, a neuropeptide unique to U. unicinctus . Results The IFT20 protein of U. unicinctus was highly conserved with that of other animals and localized at the ciliary base in the trochophore and the segmentation larvae of U. unicinctus . It was determined that the neuropeptide FILa1 inhibits IFT20 expression through the cAPM-PKA-CREB and Ca 2+ pathways, which in turn triggers larval settlement. Knockdown the mRNA level of IFT20 resulted in a reduction in the number of vesicles at the ciliary base, the β-tubulin protein synthesis, the number and length of cilia, and the beat frequency of the circumoral cilia. Finally, the settlement rate of the larvae in the IFT20 -dsRNA group increased by 3.64 times and 2.88 times compared to the control group at 48 and 72 h, respectively. Conclusion Our findings provide new insights into the function of IFT20 and the signaling pathways through which neuropeptides regulate ciliary gene expression during larval settlement.

Effects of Fe/Mg-modified lignocellulosic biochar on in vitro ruminal microorganism fermentation of corn stover - Yuping Liu; Jiyu Sun; Taotao Zhao; Lin Wang; Chenyu Zhao; Jingjing Fu; Dawei Li; Haiye Yu (Bioresource Technology, 2025)

Experimental investigations in the effect of passive gyro stabilizers on the pitch motion of a semi-submersible floating wind turbine - Junlei Wang; Haoran Li; Jisheng Zhang; Dawei Guan; Xiangfeng Lin; Hao Chen (Ocean Engineering, 2025)

Field-scale simulation of runoff and water quality in a paddy field: A study of novel RWQSPad model - Dawei Lin; Baolin Su; Wuzhi Yang; Ningbo Huang; Kun Zhao; Yutang Guan; Ya Liao; Jingwen Zhou (Ecological Modelling, 2025)

Shear behaviour of steel-headed stud connectors in engineered cementitious composite (ECC) bridge deck under positive and negative moments - Dawei Gu; Bo Jiang; Jingting Lin; Li Xu; Jinlong Pan (Engineering Structures, 2025)

Fabrication of Ag based Surface Enhanced Raman Scattering substrates with periodic mask arrays by electron beam deposition - Tian Xing; Jiawei Wang; Jiaqing Wei; Xingxing Du; Ruijin Hong; Chunxian Tao; Qi Wang; Hui Lin; Zhaoxia Han; Dawei Zhang (Analytica Chimica Acta, 2025)

Shear performance of perfobond leiste (PBL) connectors in engineered cementitious composites (ECC) - Dawei Gu; Jingting Lin; Bo Jiang; Huan Chen; Li Xu; Jinlong Pan (Engineering Structures, 2025)

Confined ionic association and its effect on Li+/Mg2+ permselective transport through the HKUST-1 nanopore - Jianduo Zhang; Fucheng Dai; Jianbo Li; Dawei He; Xuan Lin; Xiaobin Jiang; Junjiang Bao; Xiaopeng Zhang; Gaohong He; Ning Zhang (Desalination, 2025)

The zinc-finger transcription factor ZFP8 negatively regulates the drought stress response in Arabidopsis thaliana by inhibiting the transcriptional activity of ABF2 - Yu'ang Tian; Yanling Li; Kelan Wang; Ran Xia; Yingru Lin; Guohui Pan; Haoyu Shi; Dawei Zhang; Honghui Lin (Journal of Plant Physiology, 2024)

Probing the capacity of a spatiotemporal deep learning model for short-term PM2.5 forecasts in a coastal urban area - Qi Liao; Mingming Zhu; Lin Wu; Dawei Wang; Zixi Wang; Si Zhang; Wudi Cao; Xiaole Pan; Jie Li; Xiao Tang; Jinyuan Xin; Yele Sun; et al. (Science of The Total Environment, 2024)

Deciphering the role of rodents in grassland degradation; A review - Mian Gul Hilal; Chao Ji; Yuyu Li; Kuanyan Tang; Huan Li; Xiaohui Liu; Kejian Lin; Dawei Wang (Journal of Environmental Management, 2024)

Corrosion-oriented self-healing coating based on ZnMg MOF for efficient corrosion protection of aluminum alloy via in-situ LDH film formation - Zhibin Chen; Jinke Wang; Lin Lu; Thee Chowwanonthapunya; Weiting Chen; Zongbao Li; Lingwei Ma; Dawei Zhang (Chemical Engineering Journal, 2024)

Optimization framework for daylight and thermal environment of retractable roof natatoriums based on generative adversarial network and genetic algorithm - Zhongqi Yu; Xinyi Ge; Zhaoxiang Fan; Yihang Zhou; Dawei Lin (Energy and Buildings, 2024)

Enhancing typhoon wave hindcasting with random forests and BP neural networks in the SWAN model - Cheng Chen; Hongkun Lin; Dawei Guan; Feng Cai; Qiaoyi Wang; Qingchun Liu (Frontiers in Marine Science, 2024)
Forecasting typhoon waves during typhoons is crucial. In this paper, the numerical wave model SWAN was enhanced through integration with two machine learning methods: the Back Propagation Neural Network and Random Forest. This integration facilitated the development of two distinct models, namely SWAN-BP and SWAN-Tree. Through correlation analysis, key input features were identified for the machine learning models. The forecasts from the SWAN model were subsequently utilized as inputs to enhance further wave prediction. These hybrid models were validated using data from Typhoon Doksuri (2023) and Typhoon Nesat (2017). The results indicated significant improvements in predicting typhoon-induced wave heights with both the SWAN-BP and SWAN-Tree models compared to the original SWAN model. Specifically, the SWAN-BP model demonstrated a 33% improvement in accuracy for the Typhoon Doksuri, whereas the SWAN-Tree model exhibited a 24% improvement. For Typhoon Nesat, the accuracy improvements were 23% for the SWAN-BP model and 21% for the SWAN-Tree model. These findings demonstrate that integrating wave numerical models with machine learning techniques can significantly enhance the predictive accuracy of numerical models. This approach offers a cost-effective means to improve the existing wave forecasting database. Traditionally, the direct use of meteorological and oceanographic data for typhoon wave prediction might be compromised by biases inherent in the numerical wave models. However, the SWAN-BP and SWAN-Tree models effectively reduce these biases, thereby providing more accurate and robust predictions. In conclusion, this paper enhances the predictive accuracy of the SWAN model and establishes a crucial foundation for more precise typhoon wave forecasting through the application of machine learning techniques.

Ground-based cloud microphysical observations at Mount Lu in the East Asian monsoon region from 2015 to 2020 - Lijun Guo; Jing Duan; Xiaopeng Zhang; Jun Li; Kai Lyu; Yi Chang; Guangxian Lu; Dawei Lin; Tian Luan; Xiaofeng Lou; Baojun Chen (Atmospheric Research, 2024)

PRC2 primes bivalent genes for transcription induction independent of histone methyltransferase activity - Meihan Gong; Ye Yuan; Zhongye Dai; Xuejiao Lv; Jiacheng Su; Dawei Huo; Lin Niu; Xu Chen; Xudong Wu (Science China Life Sciences, 2024)

Convergent Neuroimaging and Molecular Signatures in Mild Cognitive Impairment and Alzheimer’s Disease: A Data-Driven Meta-Analysis with N = 3,118 - Xiaopeng Kang; Dawei Wang; Jiaji Lin; Hongxiang Yao; Kun Zhao; Chengyuan Song; Pindong Chen; Yida Qu; Hongwei Yang; Zengqiang Zhang; Bo Zhou; Tong Han; et al. (Neuroscience Bulletin, 2024)
The current study aimed to evaluate the susceptibility to regional brain atrophy and its biological mechanism in Alzheimer’s disease (AD). We conducted data-driven meta-analyses to combine 3,118 structural magnetic resonance images from three datasets to obtain robust atrophy patterns. Then we introduced a set of radiogenomic analyses to investigate the biological basis of the atrophy patterns in AD. Our results showed that the hippocampus and amygdala exhibit the most severe atrophy, followed by the temporal, frontal, and occipital lobes in mild cognitive impairment (MCI) and AD. The extent of atrophy in MCI was less severe than that in AD. A series of biological processes related to the glutamate signaling pathway, cellular stress response, and synapse structure and function were investigated through gene set enrichment analysis. Our study contributes to understanding the manifestations of atrophy and a deeper understanding of the pathophysiological processes that contribute to atrophy, providing new insight for further clinical research on AD.

Kiwifruit resistance to gray mold is enhanced by yeast-induced modulation of the endophytic microbiome - Qinhong Liao; Yu Zhao; Zhenshuo Wang; Longfeng Yu; Qiqian Su; Jiaoqian Li; Anran Yuan; Junkui Wang; Dawei Tian; Chenglin Lin; Xiaoya Huang; Wenhua Li; et al. (Science of The Total Environment, 2024)

A single-electrode evaluation method used for analyzing the working mechanism and capability of integrated membrane capacitive deionization - Qinghao Wu; Qifeng Wang; Chen Yu; Shanfu Lu; Kun Lin; Yan Xiang; Kuichang Zuo; Doron Aurbach; Dawei Liang (Desalination, 2024)

Genome-wide profiling of DNA methylome and transcriptome reveals epigenetic regulation of Urechis unicinctus response to sulfide stress - Wenqing Zhang; Long Zhang; Yuxin Feng; Dawei Lin; Zhi Yang; Zhifeng Zhang; Yubin Ma (Science of The Total Environment, 2024)

Ultrasonic-enhanced selective arsenic removal and sulfide conversion from iron slag - Yuefeng Chen; Guo Lin; Shixing Wang; Hongliang Liu; Likang Fu; Dawei Xiang; Manying Zhu (Journal of Cleaner Production, 2024)

Enhancing microdroplet array generation via heterogeneous inner surface Modification: Biomimetic & hydrophobic approach - Lin Du; Zijian Zhou; Jie Wang; Dawei Zhang; Yuxin Li; Jia Zhou; Dalei Jing (Chemical Engineering Journal, 2024)

Changes in Sea Level along the South China Sea Coast Based on the Homogenized Tide Gauge Data - Yan Li; Lin Mu; Dawei You; Jiaying Wang; Qianru Niu; Xiaomei Liao (Journal of Marine Science and Engineering, 2024)
To estimate the changes in the annual mean sea level (MSL) and extreme sea levels (ESLs), the largest collection of tide gauge records from 10 tidal stations along the northern coast of the South China Sea (SCS) were analyzed in this study. Here, all the tide gauge records had been homogenized by a two-step process involving the detection of inhomogeneities, that is, breakpoints caused by non-climatic changes and the application of the adjustment. The study’s conclusions, based on the homogenized tide gauge records, can be summarized as follows: The instrument change and station relocation are the main causes for the identified inhomogeneities. From 1989 to 2018, the sea level along the SCS was at an average rate of 4.0 mm per year, as measured by the homogenized tide gauges. The ESLs from the nine tidal stations rose notably with interannual fluctuations, except for the XSA station. Additionally, the ESLs exhibited substantial decadal variations. The ESLs rose along the northern coast of the SCS and were accelerated at most stations throughout the whole study period, especially after the 1980s. There were significant positive correlations between the ESL and the annual MSL at most tide gauges. The MSL’s changes, especially long-term changes, play an important role in the change in ESLs.

Scour processes around a horizontal axial tidal stream turbine supported by the tripod foundation - Xiangfeng Lin; Jisheng Zhang; Dawei Guan; Jinhai Zheng; Yuquan Zhang; Emmanuel Fernandez-Rodriguez; Luchao Gao (Ocean Engineering, 2024)

Ammonia release characteristics during desulfurization wastewater evaporation: Mechanisms and implications - Heng Chen; Dawei Hou; Zhihao Li; Lingxiao Zhan; Lijian Jin; Suoqi Zheng; Yurui Wang; Hao Wu; Ning Zhao; Liliang Lin; Linjun Yang (Journal of Water Process Engineering, 2024)

Anthropogenic influence has significantly affected snowfall changes in Eurasia - Wenqing Lin; Huopo Chen; Weiqi Wang; Dawei Zhang; Fan Wang; Wuxia Bi (Atmospheric Research, 2024)

Immobilized Z-scheme Ag|AgBr/Ag/FeTiO3 nanocomposite film photocatalyst for visible-light-driven photocatalytic degradation of norfloxacin with simultaneous hydrogen evolution and mechanism perspective - Hongfeng Yao; Honglu Zhang; Chun Lin; Dawei Fang; Mei Tie; Jun Wang; Zhaohong Zhang (Journal of Environmental Chemical Engineering, 2023)

Evolution from natural resources to trade dynamics: Paving the way for sustainable development goals - Dawei Wang; Yi Lin; Junhao Kou (Resources Policy, 2023)

Wet dispersion of graphene assisted constructing multiple interface pores of PVDF hollow fiber membranes via melt-spinning and stretching - Dawei Ji; Weijia Lin; Guangwu Sun; Xuyong Tian; Xixian Ma; Changfa Xiao (Journal of Environmental Chemical Engineering, 2023)

Event-triggered coordinated trajectory tracking control for multiple fully-actuated MSVs under prescribed performance constraints and limited transmission resources - Chonglang Lai; Xiaogong Lin; Ziyi Su; Dawei Zhao (Ocean Engineering, 2023)

Genome-wide identification of R2R3-MYB transcription factor family in Docynia delavayi (Franch.) Schneid and its expression analysis during the fruit development - Jinhong Tian; JunXia Shu; Liu Xu; Huajin Ya; Lin Yang; Siguang Li; Dawei Wang (Food Bioscience, 2023)

V-ATPase V0 subunit activation mediates maduramicin-induced methuosis through blocking endolysosomal trafficking in vitro and in vivo - Yuling Zheng; Jing Xiao; Junqi Wang; Bin Dong; Dawei Guo; Hui Ji; Haifeng Sun; Lin Peng; Shanxiang Jiang; Xiuge Gao (Food and Chemical Toxicology, 2023)

PCSK9 Inhibition Regulates Infarction-Induced Cardiac Myofibroblast Transdifferentiation via Notch1 Signaling - Chen Wu; Dawei Lin; Jian Ji; Yiweng Jiang; Feng Jiang; Yaosheng Wang (Cell Biochemistry and Biophysics, 2023)

Semi-theoretical prediction for equilibrium scour depth of a mono-pile supported tidal stream turbine - Xiangfeng Lin; Jisheng Zhang; Jinhai Zheng; Dawei Guan; Risheng Wang (Ocean Engineering, 2023)

Au/SiNCA-based SERS analysis coupled with machine learning for the early-stage diagnosis of cisplatin-induced liver injury - Shengjie Ge; Gaoyang Chen; Dawei Cao; Hechuan Lin; Ziyang Liu; Meng Yu; Shiyi Wang; Zhigang Wang; Ming Zhou (Analytica Chimica Acta, 2023)

Cold spells linked with respiratory disease hospitalization, length of hospital stay, and hospital expenses: Exploring cumulative and harvesting effects - Jin Feng; Dawei Cao; Dashan Zheng; Zhengmin (Min) Qian; Cunrui Huang; Huiqing Shen; Yi Liu; Qiyong Liu; Jimin Sun; Guangyuan Jiao; Xiaoran Yang; Stephen Edward McMillin; et al. (Science of The Total Environment, 2023)

Improved dynamic event-triggered anti-unwinding control for autonomous underwater vehicles - Ziyi Su; Xiaogong Lin; Bing Huang; Dawei Zhao; Han Sun (Ocean Engineering, 2023)

Metal-organic framework nanocrystals enabled efficient and durable two-step perovskite photovoltaics - Xiao Liang; Kang Zhou; Dawei Duan; Fei Wang; Chuangye Ge; Xianfang Zhou; Mingjian Yuan; Yumeng Shi; Haoran Lin; Quanyao Zhu; Gang Li; Hanlin Hu (Chemical Engineering Journal, 2023)

Scour processes around a mono-pile foundation under bi-directional flow considering effects from a rotating turbine - Xiangfeng Lin; Jisheng Zhang; Dawei Guan; Jinhai Zheng; Hailong Wang; Bo Liu (Ocean Engineering, 2023)

A high-efficient anisotropic continuum model for the optimization of heat transfer and chemical reaction in a packed-bed water gas shift reactor - Bo Jiang; Haonan Wang; Kewei Yu; Jing Ma; Wang Si-ma; Yuming Gao; Lin Li; Xinwei Zhang; Huiru Cui; Dawei Tang (Fuel, 2023)

Multiple arching in cohesion–friction soils: Insights from deformation behavior and failure mechanisms using FEM-SPH approach - Hao Xiong; Yuanyi Qiu; Xing-Tao Lin; Xiangsheng Chen; Dawei Huang (Computers and Geotechnics, 2023)

Effect of hydrothermal pretreatment and compound microbial agents on compost maturity and gaseous emissions during aerobic composting of kitchen waste - Ting Xie; Zhaohan Zhang; Dawei Zhang; Chunzhong Wei; Yong Lin; Rongwei Feng; Jun Nan; Yujie Feng (Science of The Total Environment, 2023)

Observer-based dynamic optimal recoil controller design for deepwater drilling riser systems - Wei Zhang; Bao-Lin Zhang; Qing-Long Han; Yue-Ting Sun; Yan Ji; Dawei Zhang; Xian-Ming Zhang (Ocean Engineering, 2023)

Mitochondrial alternative oxidase enhanced ABA-mediated drought tolerance in Solanum lycopersicum - Kang Qiao; Xiuhong Yao; Zuxu Zhou; Jiawei Xiong; Ke Fang; Jiayi Lan; Fei Xu; Xingguang Deng; Dawei Zhang; Honghui Lin (Journal of Plant Physiology, 2023)

Rapid detection and identification of fungi in grain crops using colloidal Au nanoparticles based on surface-enhanced Raman scattering and multivariate statistical analysis - Huiqin Wang; Mengjia Liu; Huimin Zhao; Xiaofeng Ren; Taifeng Lin; Ping Zhang; Dawei Zheng (World Journal of Microbiology and Biotechnology, 2023)

PMT gain self-adjustment system for high-accuracy echo signal detection - Guoqing Zhou; Chao Xu; Haotian Zhang; Xiang Zhou; Dawei Zhao; Gongbei Wu; Jinchun Lin; Zhexian Liu; Jiazhi Yang; Xueqin Nong; Lieping Zhang (International Journal of Remote Sensing, 2022)

Construction of a core germplasm bank of upland cotton (Gossypium hirsutum L.) based on phenotype, genotype and favorable alleles - Peng Han; Xiaomin Tian; Ying Wang; Cong Huang; Yizan Ma; Xiaofeng Zhou; Yu Yu; Dawei Zhang; Haijiang Xu; Yang Cao; Bo Zhu; Zhenxiu Feng; et al. (Genetic Resources and Crop Evolution, 2022)

Integrated analysis of the transcriptome and metabolome in young and mature leaves of Yunnanopilia longistaminea - Yuchang Wang; Bingqi Shen; Lin Yang; Dawei Wang (Plant Biotechnology Reports, 2022)

Research on infrared dim and small target detection algorithm based on frequency domain difference - Leihong Zhang; Haiqing Miao; Jian Chen; Weihong Lin; Runchu Xu; Dawei Zhang (International Journal of Remote Sensing, 2022)

On the Two Successive Supercold Waves Straddling the End of 2020 and the Beginning of 2021 - Cholaw Bueh; Jingbei Peng; Dawei Lin; Bomin Chen (Advances in Atmospheric Sciences, 2022)

Molecular epidemiology of type I and II feline coronavirus from cats with suspected feline infectious peritonitis in China between 2019 and 2021 - Lishan Lin; Dawei Yao; Lei Wu; Rubin Fan; Yang Liu; Zhenlei Zhou (Archives of Virology, 2022)

Evaluation of reanalysis surface wind products with quality-assured buoy wind measurements along the north coast of the South China Sea - Jing Cha; Xinyu Lin; Xiaogang Guo; Xiaofang Wan; Dawei You (Acta Oceanologica Sinica, 2021)

Rapid assessment of landslide risk level based on deep learning - Fei Tan; Jin Yu; Yu-Yong Jiao; Dawei Lin; Jiahe Lv; Yi Cheng (Arabian Journal of Geosciences, 2021)

Quantitative assessment on soil concentration of heavy metal–contaminated soil with various sample pretreatment techniques and detection methods - Fei Pan; Yong Yu; Lei Yu; Hailan Lin; Yeyao Wang; Linlin Zhang; Dawei Pan; Rilong Zhu (Environmental Monitoring and Assessment, 2020)

A gain-of-function mutation in Brassinosteroid-insensitive 2 alters Arabidopsis floral organ development by altering auxin levels - Taotao Li; Xinke Kang; Lin Wei; Dawei Zhang; Honghui Lin (Plant Cell Reports, 2020)

NAP is involved in GA-mediated chlorophyll degradation and leaf senescence by interacting with DELLAs in Arabidopsis - Wei Lei; Yan Li; Xiuhong Yao; Kang Qiao; Lin Wei; Baohui Liu; Dawei Zhang; Honghui Lin (Plant Cell Reports, 2020)

Landslide detection in La Paz City (Bolivia) based on time series analysis of InSAR data - Chao Huang Lin; Dawei Liu; Guang Liu (International Journal of Remote Sensing, 2019)

QTL analysis of nodule traits and the identification of loci interacting with the type III secretion system in soybean - Jingyi Zhu; Jinhui Wang; Qingying Li; Jieqi Wang; Yang Liu; Jianyi Li; Lin Chen; Yan Shi; Shuping Li; Yongqian Zhang; Xueying Liu; Chao Ma; et al. (Molecular Genetics and Genomics, 2019)

Dynamic expressions of hypothalamic genes regulate seasonal breeding in a natural rodent population - Dawei Wang; Ning Li; Lin Tian; Fei Ren; Zhengguang Li; Yan Chen; Lan Liu; Xiangfa Hu; Xuechang Zhang; Ying Song; Roelof A. Hut; Xiao‐Hui Liu (Molecular Ecology, 2019)
Seasonal breeding is a universal reproductive strategy in many animals. Hypothalamic genes, especially type 2 and 3 iodothyronine deiodinases ( Dio2 / 3 ), RFamide‐related peptide 3 ( Rfrp‐3 ), kisspeptin ( Kiss‐1 ) and gonadotropin‐releasing hormone ( GnRH ), are involved in a photoperiodic pathway that encodes seasonal signals from day length in many vertebrate species. However, the seasonal expression patterns of these genes in wild mammals are less studied. Here, we present a four‐year field investigation to reveal seasonal rhythm and age‐dependent reproductive activity in male Brandt's voles ( Lasiopodomys brandtii ) and to detect relationships among seasonal expression profiles of hypothalamic genes, testicular activity, age and annual day length. From breeding season (April) to nonbreeding season (October), adult male voles displayed a synchronous peak in gonadal activity with annual day length around summer solstice, which was jointly caused by age structure shifts and age‐dependent gonadal development patterns. Overwintered males maintained reproductive activity until late in the breeding season, whereas most newborn males terminated gonadal development completely, except for a minority of males born early in spring. Consistently, the synchronous and opposite expression profiles of Dio2/3 suggest their central function to decode photoperiodic signals and to predict the onset of the nonbreeding season. Moreover, changes in Dio2/3 signals may guide the actions of Kiss‐1 and Rfrp‐3 to regulate the age‐dependent divergence of reproductive strategy in wild Brandt's vole. Our results provide evidence on how hypothalamic photoperiod genes regulate seasonal breeding in a natural rodent population.

Geochemical Appraisal of Chemical Weathering and Metal Contamination in Coastal Surface Sediments, Off Northwest Hainan Island, the Gulf of Tonkin - Dawei Liu; Baozhi Lin; Selvaraj Kandasamy; Huawei Wang; Qianqian Liu; Wenbin Zou; Aimei Zhu; Jianjun Zou; Jiann-Yuh Lou; Xuefa Shi (Frontiers in Marine Science, 2019)

Nodulation and Genomic Capacity of a Novel High-Latitude Bradyrhizobium japonicum HLNEAU001 - Yan Shi; Jianyi Li; Jinhui Wang; Rongsheng Zhu; Shuping Li; Qingying Li; Lin Chen; Jingyi Zhu; Jianan Zou; Jieqi Wang; Huilin Chang; Chao Ma; et al. (Journal of Soil Science and Plant Nutrition, 2019)

The fecal virome of red-crowned cranes - Yan Wang; Shixing Yang; Dawei Liu; Chenglin Zhou; Wang Li; Yuan Lin; Xiaochun Wang; Quan Shen; Hua Wang; Chuang Li; Minghui Zong; Yuzhu Ding; et al. (Archives of Virology, 2019)

Effect of Aluminum Exposure on Glucose Metabolism and Its Mechanism in Rats - Xi Wei; Hua Wei; Dawei Yang; Dong Li; Xianli Yang; Mingjie He; Erbing Lin; Biaoliang Wu (Biological Trace Element Research, 2018)

Mining for genes encoding proteins associated with NopL of Sinorhizobium fredii HH103 using quantitative trait loci in soybean (Glycine max Merr.) recombinant inbred lines - Yanjiao Zhang; Xueying Liu; Lin Chen; Ying Fu; Changyu Li; Zhaoming Qi; Jianan Zou; Rongsheng Zhu; Shuping Li; Wei Wei; Jinhui Wang; Huilin Chang; et al. (Plant and Soil, 2018)

Transcriptome profile analysis reveals cardiotoxicity of maduramicin in primary chicken myocardial cells - Xiuge Gao; Lin Peng; Xiangchun Ruan; Xin Chen; Hui Ji; Junxiao Ma; Han Ni; Shanxiang Jiang; Dawei Guo (Archives of Toxicology, 2018)

A CRISPR/Cas9 toolkit for efficient targeted base editing to induce genetic variations in rice - Bin Ren; Fang Yan; Yongjie Kuang; Na Li; Dawei Zhang; Honghui Lin; Huanbin Zhou (Science China Life Sciences, 2017)

T2 relaxation time measurements in the brains of scalded rats - Tao Jiang; Liqi Xie; Xin Lou; Dawei Li; Zhiye Chen; Huafeng Xiao; Lin Ma (Science China Life Sciences, 2017)

Synthesis and evaluation of novel benzene-ethanol bearing 1,2,4-triazole derivatives as potential antimicrobial agents - Bochao Li; Dawei Zhang; Yumin Zhang; Dan Jiang; Shuang Li; Wei Lei; Huiying Wang; Feng Lin (Medicinal Chemistry Research, 2017)

Analysis of chemical characteristics of PM2.5 in Beijing over a 1-year period - Zhanshan Wang; Dawei Zhang; Baoxian Liu; Yunting Li; Tian Chen; Feng Sun; Dongyan Yang; Yunping Liang; Miao Chang; Liu Yang; Anguo Lin (Journal of Atmospheric Chemistry, 2016)

Interannual variability of summer rainfall over the northern part of China and the related circulation features - Cholaw Bueh; Yan Li; Dawei Lin; Yi Lian (Journal of Meteorological Research, 2016)

Erratum to: Microsatellite records for volume 7, issue 4 - Rose Komugisha Basiita; J. Henrich Bruggemann; Nianhui Cai; Conchi Cáliz-Campal; Chen Chen; Jiawei Chen; L. Cizek; Pedro J. Cordero; Deborah A. Dawson; Yandong Ding; L. Drag; Anan Duan; et al. (Conservation Genetics Resources, 2016)

Cathodic stripping voltammetric determination of chromium in coastal waters on cubic Nano-titanium carbide loaded gold nanoparticles modified electrode - Haitao Han; Dawei Pan; Dongyan Liu; Xueping Hu; Mingyue Lin; Fei Li (Frontiers in Marine Science, 2015)

Regression Analysis of Non-iatrogenic Factors That Determine Adherence to Radiation Therapy - Xiangzhao Bu; Xuemei Fan; Dawei Hao; Lin Guo; Chengjun Wu; Chong Zhou (Cell Biochemistry and Biophysics, 2015)

Folate and TAT Peptide Co-Modified Liposomes Exhibit Receptor-Dependent Highly Efficient Intracellular Transport of Payload In Vitro and In Vivo - Yaqin Zhu; Liang Cheng; Lifang Cheng; Fazhen Huang; Qing Hu; Ling Li; Chenmin Tian; Lin Wei; Dawei Chen (Pharmaceutical Research, 2014)

CD4+CD25+ regulatory T cells are not required for mesenchymal stem cell function in fully MHC-mismatched mouse cardiac transplantation - Xiaofeng Jiang; Chen Liu; Jianpeng Hao; Dawei Guo; Jinshuai Guo; Junchao Yao; Kun Jiang; Zheming Cui; Lei Zhu; Wenyu Sun; Lin Lin; Jian Liang (Cell and Tissue Research, 2014)

Influence of TLR4 rs1927907 locus polymorphisms on tacrolimus pharmacokinetics in the early stage after liver transplantation - Zhaowen Wang; Shaohan Wu; Dawei Chen; Feng Guo; Lin Zhong; Junwei Fan; Zhihai Peng (European Journal of Clinical Pharmacology, 2014)

Fine mapping and candidate gene analysis of the novel thermo-sensitive genic male sterility tms9-1 gene in rice - Yongbin Qi; Qinglong Liu; Lin Zhang; Bizeng Mao; Dawei Yan; Qingsheng Jin; Zuhua He (Theoretical and Applied Genetics, 2014)

Ex-situ enzyme activity and bacterial community diversity through soil depth profiles in penguin and seal colonies on Vestfold Hills, East Antarctica - Dawei Ma; Renbin Zhu; Wei Ding; Congcong Shen; Haiyan Chu; Xiangui Lin (Polar Biology, 2013)

Remote estimation of phycocyanin (PC) for inland waters coupled with YSI PC fluorescence probe - Kaishan Song; Lin Li; Lenore Tedesco; Nicole Clercin; Bob Hall; Shuai Li; Kun Shi; Dawei Liu; Ying Sun (Environmental Science and Pollution Research, 2013)

Large-scale collection and annotation of gene models for date palm (Phoenix dactylifera, L.) - Guangyu Zhang; Linlin Pan; Yuxin Yin; Wanfei Liu; Dawei Huang; Tongwu Zhang; Lei Wang; Chengqi Xin; Qiang Lin; Gaoyuan Sun; Mohammed M. Ba Abdullah; Xiaowei Zhang; et al. (Plant Molecular Biology, 2012)

Simultaneous Effects of Lead and Cadmium on Primary Cultures of Rat Proximal Tubular Cells: Interaction of Apoptosis and Oxidative Stress - Lin Wang; Heng Wang; Jingui Li; Dawei Chen; Zongping Liu (Archives of Environmental Contamination and Toxicology, 2011)

Association of polymorphisms in folate metabolic genes and prostate cancer risk: a case-control study in a Chinese population - Dawei Cai; Lin Ning; Chunyu Pan; Xuefeng Liu; Renge Bu; Xiaonan Chen; Kefeng Wang; Yang Cheng; Bin Wu (Journal of Genetics, 2010)

A multifunctional HTDMA system with a robust temperature control - Xingnan Ye; Tianyi Chen; Dawei Hu; Xin Yang; Jianmin Chen; Renyi Zhang; Alexei F. Khakuziv; Lin Wang (Advances in Atmospheric Sciences, 2009)

Effects of Lead and/or Cadmium on the Expression of Metallothionein in the Kidney of Rats - Lin Wang; Dawei Chen; Heng Wang; Zongping Liu (Biological Trace Element Research, 2009)

Oxidative stress and apoptotic changes in primary cultures of rat proximal tubular cells exposed to lead - Lin Wang; Heng Wang; Maozhi Hu; Jin Cao; Dawei Chen; Zongping Liu (Archives of Toxicology, 2009)

Role of Oxidative Stress, Apoptosis, and Intracellular Homeostasis in Primary Cultures of Rat Proximal Tubular Cells Exposed to Cadmium - Lin Wang; Jin Cao; Dawei Chen; Xuezhong Liu; Hao Lu; Zongping Liu (Biological Trace Element Research, 2009)

Meta-analysis shows association between the tryptophan hydroxylase (TPH) gene and schizophrenia - Dawei Li; Lin He (Human Genetics, 2006)

Further clarification of the contribution of the tryptophan hydroxylase (TPH) gene to suicidal behavior using systematic allelic and genotypic meta-analyses - Dawei Li; Lin He (Human Genetics, 2006)

Involvement of histone hypoacetylation in Ni2+-induced bcl-2 down-regulation and human hepatoma cell apoptosis - Jiuhong Kang; Dawei Zhang; Jie Chen; Changjun Lin; Qing Liu (JBIC Journal of Biological Inorganic Chemistry, 2004)